A NEW SPECIES OF AESCHYNANTHUS (GESNERIACEAE) FROM VIETNAM - Middleton, D. J.; Atkins, H. J. (Edinburgh Journal of Botany, 2018)
The new species Aeschynanthus scottii D.J.Middleton & H.J.Atkins from Vietnam is described.